2022
DOI: 10.1142/s1363919622400242
|View full text |Cite
|
Sign up to set email alerts
|

How Companies Innovate Business Models and Supply Chains for a Circular Economy: A Multiple-Case Study and Framework

Abstract: To implement a circular economy (CE), companies are pushed to innovate, respectively, their business models, from a micro-perspective, and their supply chains, from a meso-perspective. Despite the increasing research on both these perspectives, there is still a knowledge gap on how companies innovate business models and supply chains for circularity. In this study, we build on innovation management, circular business model (CBM), and circular supply chain (CSC) literatures and develop a theory-based framework … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…All the identified CBMI tools focused on the ideation and design stage of the BMI process and were, unsurprisingly, business-oriented. All the tools are generalisable with the exception of three (Averina et al, 2022;Huynh, 2022;Kaipainen et al, 2022) that were specific to the context of a particular industry (i.e.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All the identified CBMI tools focused on the ideation and design stage of the BMI process and were, unsurprisingly, business-oriented. All the tools are generalisable with the exception of three (Averina et al, 2022;Huynh, 2022;Kaipainen et al, 2022) that were specific to the context of a particular industry (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, the authors usually present and analyse the application of a single tool rather than toolboxes. process-innovation) and required circular supply chain innovation (from incremental to radical) (Kaipainen et al, 2022) and visualise communication flows between different stakeholders (Huynh, 2022). Some combine CBM patterns, life cycle assessment and value chain aspects to support strategic decisions regarding the development of circular value architectures (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…These because they support other firms by providing long-lasting clothes but are not central to the CBM implementation. This highlights the importance of exploring constellations of actors that make CBMs possible (Kanda et al, 2021; Kaipainen et al, 2022) and calls for further research on issues of centrality, ecosystems and supporting roles in a circular economy. In general, we concluded that incumbents are more active upstream in relation to the customer, although they do have various upcycling and recycling projects.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent work by Kanda et al (2021) has argued that the boundaries of a business model should be wider than the perspective of a single firm, and that circulating resources is usually made possible by a business ecosystem. Kaipainen et al (2022) also emphasise the importance of circular supply chains. Thus, we categorise these firms as CBM supporters, which we define as a firm that does not implement a CBM but is part of an ecosystem that supports another firm implementing it.…”
Section: Cbms In the Workwear Industrymentioning
confidence: 97%
“…Moving the construction industry towards circularity requires creating comprehensive networks that include all stakeholders in the supply chain, from design and raw material suppliers to users, including service providers, recyclers, and related information flows [94]. In the CE context, stakeholder engagement through relationship development, communication, and learning practices may promote the adoption and development of circular innovations, circular-oriented decision making, circular value capture models, co-creation, and the diffusion of sustainability culture via marketing, and educational activities are crucial [95].…”
mentioning
confidence: 99%